Cognitive functioning in children and adults with Smith-Magenis syndrome - Osório, Ana Alexandra Caldas (2012)
Smith-Magenis Syndrome (SMS) is a genetic neurodevelopmental disorder caused by a microdeletion on chromosome 17p11.2. This syndrome is characterized by a distinctive profile of physical, medical and neuropsychological characteristics. The latter include general mental disability, with the majority of individuals falling within the mild to moderate range. This study reports a detailed cognitive assessment of children and adults with SMS with the use of the Wechsler intelligence scales at three distinct levels of analysis: full scale IQ, factorial indices, and subtests. Child and adult samples were each compared to samples of age and gender-matched typically developing individuals. To our knowledge, this is the first study to systematically analyse the cognitive profile of individuals with SMS in Southern Europe. The present study confirmed mental disability, particularly within the moderate category, as a consistent feature of children and adults with SMS. Furthermore, both child and adult samples evidenced significant impairments in all four indices when compared with their typically developing counterparts. A specific pattern of strengths and weaknesses was discernible for both samples, with Verbal Comprehension emerging as a relative strength, whereas Working Memory appeared as a relative weakness. Finally, with the exception of two subtests in the perceptual domain, we found no evidence for a general cognitive decline with age.